Pengaruh Permainan Tradisional Bentengan dan Gobak Sodor Terhadap Kelincahan Siswa Mi Nw Lingkung - Lalu Herwandi Wirahman; Mujriah Mujriah; Muhamad Ikhsan (Universitas Hamzanwadi, 2026)
Traditional games are increasingly eroded by technological developments, causing elementary school students' physical activity to decline and impacting low agility. This study aims to determine the effect of traditional games bentengan and gobak sodor on improving agility of students at MI NW Lingkung. The research method used an experiment with One Group Pretest-Posttest Design. The sample consisted of 24 fifth-grade students selected using total sampling technique. Agility was measured using the 4 × 10 meter Shuttle Run test during pretest and posttest. The treatment program was conducted for 8 meetings. Data analysis used Shapiro-Wilk normality test, Levene's Test homogeneity test, Paired Sample t-Test (α = 0.05), as well as Cohen's d effect size and N-Gain test. The results showed the average time decreased from 9.01 seconds to 6.68 seconds with an increase of 25.88%. The Paired Sample t-Test showed a significance value of 0.000 (p < 0.05), Cohen's d of 2.44 (very large effect), and N-Gain of 0.56 (moderate category). All students experienced improved agility. The conclusion of this study is that the traditional games bentengan and gobak sodor are effective in improving elementary school students' agility and can be used as an attractive, inexpensive, and enjoyable alternative for physical education learning.